Dysregulated Immunometabolism Is Associated with the Generation of Myeloid-Derived Suppressor Cells in Staphylococcus aureus Chronic Infection - Oliver Dietrich (Karger Publishers, 2021)
Myeloid-derived suppressor cells (MDSCs) are a compendium of immature myeloid cells that exhibit potent T-cell suppressive capacity and expand during pathological conditions such as cancer and chronic infections. Although well-characterized in cancer, the physiology of MDSCs in the infection setting remains enigmatic. Here, we integrated single-cell RNA sequencing (scRNA-seq) and functional metabolic profiling to gain deeper insights into the factors governing the generation and maintenance of MDSCs in chronic Staphylococcus aureus infection. We found that MDSCs originate not only in the bone marrow but also at extramedullary sites in S. aureus-infected mice. scRNA-seq showed that infection-driven MDSCs encompass a spectrum of myeloid precursors in different stages of differentiation, ranging from promyelocytes to mature neutrophils. Furthermore, the scRNA-seq analysis has also uncovered valuable phenotypic markers to distinguish mature myeloid cells from immature MDSCs. Metabolic profiling indicates that MDSCs exhibit high glycolytic activity and high glucose consumption rates, which are required for undergoing terminal maturation. However, rapid glucose consumption by MDSCs added to infection-induced perturbations in the glucose supplies in infected mice hinders the terminal maturation of MDSCs and promotes their accumulation in an immature stage. In a proof-of-concept in vivo experiment, we demonstrate the beneficial effect of increasing glucose availability in promoting MDSC terminal differentiation in infected mice. Our results provide valuable information of how metabolic alterations induced by infection influence reprogramming and differentiation of MDSCs.